Preparation method and application of magnesium-doped alumina catalyst carrier

By doping magnesium in situ in the sol process of the alumina catalyst support, combined with gelation and hydrothermal treatment, a magnesium-doped alumina catalyst support was prepared, which solved the problem of insufficient catalytic activity of the existing alumina support, and achieved more efficient catalytic performance and better industrial applicability.

CN119793432APending Publication Date: 2025-04-11HUBEI XINGFA CHEM GRP CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411842214.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing alumina catalyst support has problems such as insufficient catalytic activity, low product yield and high cost in catalytic hydrogenation reactions, and the uneven doping of magnesium-aluminum spinel support affects the catalytic performance.

Method used

By using phthalinated alumina as raw material, using alkaline earth metal magnesium doped in situ in the sol process, combined with gelation and hydrothermal treatment, a magnesium-doped alumina catalyst support is prepared to improve the electronic structure and pore structure characteristics of the support.

Benefits of technology

The specific surface area and pore size distribution of the catalyst support are improved, the adsorption capacity of the active ingredients and metal-support interaction are enhanced, and the catalytic activity and selectivity are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793432A_ABST
    Figure CN119793432A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of catalyst carriers, and particularly discloses a preparation method and application of a magnesium-doped alumina catalyst carrier, and the preparation method comprises the following steps: S1, taking pseudo-boehmite as a raw material, adding nitric acid, and mixing and dispersing; s2, magnesium salt is dissolved with water to prepare a solution, the solution is added into the material obtained in the S1 to be mixed evenly, and then a precipitator is added to be mixed evenly; s3, performing hydrothermal reaction on the material obtained in S2, centrifuging, washing, drying, and finally sintering to obtain the magnesium-doped aluminum oxide catalyst carrier. The alkaline earth metal magnesium is doped in situ in the process of synthesizing the aluminum oxide catalyst carrier, the surface pH value of the aluminum oxide carrier is adjusted, more hydroxyl sites can be generated on the surface of the modified aluminum oxide carrier in a hydrothermal mode, adsorption of active ingredients is facilitated, and interaction between the carrier and metal particles is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts, and in particular to a preparation method and application of a magnesium-doped alumina catalyst carrier. Background Art

[0002] Alumina, due to its large specific surface area and rich pore structure, is widely used as a catalyst or catalyst carrier in the fields of hydrogenation, catalytic cracking, catalytic combustion, etc. in the chemical industry. In catalytic hydrogenation reactions, the catalyst is generally a supported catalyst, which consists of an active component and a catalyst carrier. The selection of an appropriate catalyst carrier has a significant effect on the electronic structure and dispersion of the active component, the activity and selectivity of the reaction, and the active component that plays a catalytic role. However, the acid-base properties of the alumina surface and the limited hydroxyl loading sites still limit the adsorption of the active component and the catalytic activity of the prepared catalyst.

[0003] Traditionally, aluminum oxide carriers are prepared from soluble aluminum salts and other additives as raw materials, which are precipitated by adding inorganic or organic alkali sources, and then collected and calcined to obtain aluminum oxide carriers. However, this method usually has the disadvantages of low product yield and high cost, and there is still room for improvement.

[0004] CN101565194A discloses a method for preparing ultrafine mesoporous magnesium-aluminum spinel, which comprises adding aluminum salt, magnesium salt and surfactant to an alkaline solution, performing hydrothermal reaction, and roasting the obtained material to obtain magnesium-aluminum spinel powder. The method is relatively simple, and the aluminum source and magnesium source exist in the form of solution, which is easy to introduce magnesium ions, but there may be aggregation or uneven distribution of magnesium ions and aluminum ions during the aging process, resulting in uneven doping of the final magnesium-aluminum spinel carrier, affecting its catalytic performance; in addition, the organic amines and surfactants used in the raw materials may affect the purity of the product or be difficult to remove, and are expensive and toxic, and are not suitable for industrial production. Summary of the invention

[0005] The present invention provides a preparation method and application of a magnesium-doped alumina catalyst carrier. The present invention uses pseudo-boehmite as a raw material, in-situ doping of alkaline earth metal magnesium in the sol process of synthesizing the alumina catalyst carrier, and then after gelation and hydrothermal treatment, it can promote the effective incorporation of magnesium ions into the alumina lattice, and generate more hydroxyl sites on the surface of the modified alumina carrier, which is beneficial to the adsorption of active ingredients and enhances the interaction between the carrier and the metal particles.

[0006] The technical solution of the present invention is to provide a method for preparing a magnesium-doped alumina catalyst carrier, comprising the following steps: S1. Using pseudo-boehmite as raw material, adding water to disperse, and adding nitric acid to mix; S2, magnesium salt is dissolved in water to make a solution, added to the material obtained in S1 and mixed, and then the precipitant is added and mixed; The materials obtained in S3 and S2 are subjected to hydrothermal reaction, then centrifuged, washed and dried, and finally sintered to obtain a magnesium-doped alumina catalyst carrier.

[0007] In a preferred embodiment, 2-5 times the mass of water is added to S1 to disperse the mixture evenly, and then an equal mass of nitric acid is added to mix and disperse the mixture to obtain an alumina sol.

[0008] Furthermore, the mass concentration of the nitric acid is 5.0-15.0wt%.

[0009] Furthermore, the mixing time in S1 is 0.5-2.0 h.

[0010] Furthermore, the magnesium salt in S2 is one or more of magnesium chloride, magnesium nitrate, magnesium sulfate, and magnesium acetate.

[0011] Furthermore, the precipitant is ammonia water, and the amount added is based on the pH of the control system being 8-12. Furthermore, the hydrothermal reaction temperature in S3 is 120-160°C and the time is 2-24h.

[0012] Furthermore, in S3, the sintering temperature is 600-900° C., and the sintering time is 1-6 hours.

[0013] Furthermore, in the magnesium-doped alumina catalyst carrier, the magnesium content, calculated as MgO, accounts for 0.5-5.0 wt % of the total mass of the catalyst carrier.

[0014] The invention relates to a magnesium-doped alumina catalyst carrier obtained by the method, wherein the specific surface area is 80-250m 2 / g, pore size is 8-50nm.

[0015] The present invention also relates to the application of the magnesium-doped alumina catalyst carrier in anthraquinone hydrogenation reaction.

[0016] The invention uses pseudo-boehmite as a raw material, in-situ doping of alkaline earth metal magnesium in the sol-gel process of synthesizing an alumina catalyst carrier, and then hydrothermally treating the alumina carrier doped with magnesium.

[0017] The beneficial effects of the present invention are: 1. The addition of magnesium can adjust the electronic structure of the alumina carrier, improve the agglomeration of active ingredients, and enhance the interaction between metal and carrier.

[0018] 2. Pseudo-boehmite is reacted with nitric acid to form a uniform alumina sol. The aluminum source has good dispersion during the reaction, and the amount of magnesium doping can be adjusted more accurately. At the same time, during the sol-gel process, the colloidal particles aggregate and cross-link to form a three-dimensional network structure, providing a pore structure, thereby optimizing the pore structure characteristics of the final carrier.

[0019] 3. Compared with the precipitation method, this method has higher controllability and flexibility in adjusting material properties. In addition, the hydrothermal method can produce more hydroxyl sites on the surface of the modified alumina carrier, which is conducive to the adsorption of active ingredients. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The transmission electron microscope image of the catalyst after the catalyst carrier prepared in Example 7 is loaded with active metal palladium and the particle size distribution diagram of the palladium particles. DETAILED DESCRIPTION

[0021] The experimental methods in the following examples are conventional methods unless otherwise specified. The raw materials, reagents, etc. used in the following examples are commercially available products unless otherwise specified.

[0022] The present invention provides a method for preparing a magnesium-doped alumina catalyst carrier, comprising the following steps: S1. Pseudo-boehmite is used as raw material, 2-5 times the weight of water is added to disperse evenly, and then nitric acid of the same weight as the pseudo-boehmite is added to mix and disperse; the mass concentration of nitric acid is 5.0-15.0wt%, and the mixing time is 0.5-2.0h.

[0023] S2, magnesium salt is dissolved in water to make a solution, added to the material obtained in S1 and mixed, and then the precipitant is added and mixed; The materials obtained from S3 and S2 are subjected to hydrothermal reaction at a reaction temperature of 120-160°C for 2-24 hours, followed by centrifugation, washing and drying, and finally sintering at a sintering temperature of 600-900°C for 1-6 hours to obtain a magnesium-doped alumina catalyst carrier.

[0024] In some embodiments, the magnesium salt includes but is not limited to one or more of magnesium chloride, magnesium nitrate, magnesium sulfate, and magnesium acetate. The precipitant is ammonia water, and the amount added is based on the pH of the system being controlled at 8-12. In some embodiments, the magnesium content in the magnesium-doped alumina catalyst carrier, calculated as MgO, accounts for 0.5-5.0 wt % of the total mass of the catalyst carrier.

[0025] The present invention is described in detail below in conjunction with specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0026] Example 1 Take 99.0g of dry pseudo-boehmite and put it into 297.0g of pure water for uniform dispersion, then add 99.0g of 10.0wt% nitric acid solution, stir and disperse for 2h; take 3.7g of magnesium nitrate, add water to dissolve to 99.0g, and then put it into the above sol; after the above sol is stirred evenly, add an appropriate amount of 25% ammonia water to adjust the pH of the sol to 10.0; then transfer the sol into a stainless steel reactor with a polytetrafluoroethylene liner, and keep it warm at 120°C for 12h; after cooling, centrifuge and wash the product three times and then dry it overnight; then roast it in an air atmosphere at 700°C for 2h, and grind it after cooling to obtain a magnesium-doped alumina catalyst carrier.

[0027] Embodiment 2: Take 99.0g of dry pseudo-boehmite and put it into 297.0g of pure water for uniform dispersion, then add 99.0g of 10.0wt% nitric acid solution, stir and disperse for 2h; take 3.7g of magnesium nitrate, add water to dissolve to 99.0g, and then put it into the above sol; after the above sol is stirred evenly, add an appropriate amount of 25% ammonia water to adjust the pH of the sol to 10.0; then transfer the sol into a stainless steel reactor with a polytetrafluoroethylene liner, and keep it warm at 120°C for 12h; after cooling, centrifuge and wash the product three times and then dry it overnight; then roast it in an air atmosphere at 800°C for 2h, and grind it after cooling to obtain a magnesium-doped alumina catalyst carrier.

[0028] Embodiment 3: Take 99.0g of dry pseudo-boehmite and put it into 297.0g of pure water for uniform dispersion, then add 99.0g of 10.0wt% nitric acid solution, stir and disperse for 2h; take 3.7g of magnesium nitrate, add water to dissolve to 99.0g, and then put it into the above sol; after the above sol is stirred evenly, add an appropriate amount of 25% ammonia water to adjust the pH of the sol to 10.0; then transfer the sol into a stainless steel reactor with a polytetrafluoroethylene liner, and keep it warm at 120°C for 12h; after cooling, centrifuge and wash the product three times and then dry it overnight; then roast it in an air atmosphere at 900°C for 2h, and grind it after cooling to obtain a magnesium-doped alumina catalyst carrier.

[0029] Embodiment 4: Take 99.0g of dry pseudo-boehmite and put it into 297.0g of pure water for uniform dispersion, then add 99.0g of 10.0wt% nitric acid solution, stir and disperse for 2h; take 3.7g of magnesium nitrate, add water to dissolve to 99.0g, and then put it into the above sol; after the above sol is stirred evenly, add an appropriate amount of 25% ammonia water to adjust the pH of the sol to 11.0; then transfer the sol into a stainless steel reactor with a polytetrafluoroethylene liner, and keep it warm at 120°C for 12h; after cooling, centrifuge and wash the product three times and then dry it overnight; then roast it in an air atmosphere at 800°C for 2h, and grind it after cooling to obtain a magnesium-doped alumina catalyst carrier.

[0030] Embodiment 5: Take 99.0g of dry pseudo-boehmite and put it into 297.0g of pure water for uniform dispersion, then add 99.0g of 10.0wt% nitric acid solution, stir and disperse for 2h; take 3.7g of magnesium nitrate, add water to dissolve to 99.0g, and then put it into the above sol; after the above sol is stirred evenly, add an appropriate amount of 25% ammonia water to adjust the pH of the sol to 12.0; then transfer the sol into a stainless steel reactor with a polytetrafluoroethylene liner, and keep it warm at 120°C for 12h; after cooling, the product is centrifuged and washed three times and then dried overnight; then it is calcined in an air atmosphere at 800°C for 2h, and ground after cooling to obtain a magnesium-doped alumina catalyst carrier.

[0031] Embodiment 6: Take 99.0g of dry pseudo-boehmite and put it into 297.0g of pure water for uniform dispersion, then add 99.0g of 10.0wt% nitric acid solution, stir and disperse for 2h; take 3.7g of magnesium nitrate, add water to dissolve to 99.0g, and then put it into the above sol; after the above sol is stirred evenly, add an appropriate amount of 25% ammonia water to adjust the pH of the sol to 10.0; then transfer the sol into a stainless steel reactor with a polytetrafluoroethylene liner, and keep it warm at 120°C for 24h; after cooling, centrifuge and wash the product three times and then dry it overnight; then roast it in an air atmosphere at 800°C for 2h, and grind it after cooling to obtain a magnesium-doped alumina catalyst carrier.

[0032] Embodiment 7: Take 98.0g of dry pseudo-boehmite and put it into 294.0g of pure water for uniform dispersion, then add 98.0g of 10.0wt% nitric acid solution, stir and disperse for 2h; take 7.4g of magnesium nitrate, dissolve it in water to 98.0g, and then put it into the above sol; after the above sol is stirred evenly, add an appropriate amount of 25% ammonia water to adjust the pH of the sol to 10.0; then transfer the sol into a stainless steel reactor with a polytetrafluoroethylene liner, and keep it warm at 120°C for 12h; after cooling, wash the product by centrifugation three times and dry it overnight; then roast it in an air atmosphere at 800°C for 2h, and grind it after cooling to obtain a magnesium-doped alumina catalyst carrier.

[0033] Embodiment 8: Take 97.0g of dry pseudo-boehmite and put it into 291.0g of pure water for uniform dispersion, then add 97.0g of 10.0wt% nitric acid solution and stir and disperse for 2h; take 11.0g of magnesium nitrate and dissolve it in water to 97.0g, and then put it into the above sol; after the above sol is stirred evenly, add an appropriate amount of 25% ammonia water to adjust the pH of the sol to 10.0; then transfer the sol into a stainless steel reactor with a polytetrafluoroethylene liner and keep it warm at 120°C for 12h; after cooling, wash the product by centrifugation three times and dry it overnight; then roast it in an air atmosphere at 800°C for 2h, and grind it after cooling to obtain a magnesium-doped alumina catalyst carrier.

[0034] Comparative Example 1 Take 100.0g of dry pseudo-boehmite and put it into 300.0g of pure water and disperse it evenly, then add 100.0g of 10.0wt% nitric acid solution and stir and disperse it for 2h; after the above sol is stirred evenly, add an appropriate amount of 25% ammonia water to adjust the pH of the sol to 10.0; then transfer the sol into a stainless steel reactor with a polytetrafluoroethylene liner and keep it warm at 120°C for 12h; after cooling, the product is centrifuged and washed three times and then dried overnight; then it is calcined in an air atmosphere at 800°C for 2h, and ground after cooling to obtain a magnesium-doped alumina catalyst carrier.

[0035] The pore structures of the catalyst supports obtained in the above examples and comparative examples were tested, and the details are shown in Table 1.

[0036] Table 1

[0037] It can be seen from Table 1 above that the pore size and pore volume of the carrier obtained after the introduction of magnesium in the sol-gel process and then hydrothermal treatment are different, which can be attributed to the introduction of magnesium. Too large pore size and pore volume may lead to structural instability of the carrier, while too small pore size and pore volume are not conducive to the adsorption of active metals and the transport of reactants. Therefore, a carrier with an appropriate pore structure should be selected to prepare the catalyst.

[0038] The catalyst carriers obtained from Example 2, Example 7, Example 8 and Comparative Example 1 were used to prepare catalysts: The above carriers were ground evenly, palladium nitrate was prepared into a palladium solution of a certain concentration, and a catalyst with a palladium content of 2.0 wt% was prepared by an equal volume impregnation method. After calcination at 400° C. and hydrogen reduction, the obtained catalyst was pressed into tablets and 60-80 mesh particles were screened, and they were recorded as Pd / MA-12, Pd / MA-22, Pd / MA-32, and Pd / A, respectively.

[0039] Catalyst Evaluation: The obtained catalyst was applied to the anthraquinone hydrogenation reaction. The evaluation of the catalyst was carried out in a high-pressure reactor. The working liquid was a mixed solvent of C9 heavy aromatics (Ar) and trioctyl phosphate (TOP) (V (C9): V (TOP) = 3:1), 2-ethylanthraquinone (eAQ) was used as a hydrogen carrier, and the eAQ content was 150g / L. 150mL of the working liquid and 5.0g of the catalyst sample were added to the high-pressure reactor. After the reactor was sealed, N2 was introduced to replace the air. The reaction temperature was set to 55°C and the speed was set to 500rpm. After the temperature stabilized, H2 was introduced and the pressure was maintained at 0.20Mpa. After a certain reaction time, 5mL of the hydrogenation liquid was added to a mixed solution of pure water and phosphoric acid, and oxygen was introduced to oxidize it thoroughly. After standing, the clear liquid was separated, and the hydrogen peroxide content in the hydrogen peroxide was titrated with a potassium permanganate solution of a standard concentration to obtain the hydrogenation efficiency.

[0040] Table 2 shows the palladium dispersion and catalytic performance of the catalysts prepared above.

[0041] Table 2

[0042] As can be seen from Table 2, the actual loading amount of the catalyst obtained by introducing magnesium into the alumina sol during the sol-gel preparation process is slightly higher than that of the undoped support. This may be attributed to the change in the support structure caused by the introduction of magnesium and the granting of more hydroxyl loading sites to the support after hydrothermal treatment. Moreover, its hydrogenation efficiency and selectivity are significantly improved compared with the undoped support.

[0043] Dark-field transmission electron micrograph of the Pd / MA-22 catalyst after the catalyst carrier prepared in Example 7 was loaded with active metal palladium and a particle size distribution diagram of the palladium particles. The white bright spots in the figure are the loaded Pd nanoparticles with an average particle size of 10.5 nm. It can be observed that most of their morphologies are spherical, and it can be seen that the Pd nanoparticles can be evenly dispersed on the carrier. The electronic environment of the alumina carrier improved by the introduction of magnesium avoids large-scale sintering of palladium nanoparticles. This dense distribution may help to improve the reaction activity.

[0044] The above embodiments describe the preferred implementation of the present invention, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a magnesium-doped alumina catalyst carrier, characterized in that: The following steps are involved: S1. Using pseudo-boehmite as raw material, adding water to disperse, and adding nitric acid to mix; S2, magnesium salt is dissolved in water to make a solution, added to the material obtained in S1 and mixed, and then the precipitant is added and mixed; The materials obtained in S3 and S2 are subjected to hydrothermal reaction, then centrifuged, washed and dried, and finally sintered to obtain a magnesium-doped alumina catalyst carrier.

2. The method according to claim 1, characterized in that: The mass concentration of the nitric acid is 5.0-15.0wt%.

3. The method according to claim 1, characterized in that: The mixing time in S1 is 0.5-2.0 h.

4. The method according to claim 1, characterized in that: The magnesium salt in S2 is one or more of magnesium chloride, magnesium nitrate, magnesium sulfate and magnesium acetate.

5. The method according to claim 1, characterized in that: The precipitant is ammonia water, and the amount added is based on the pH of the control system being 8-12.

6. The method according to claim 1, characterized in that: The hydrothermal reaction temperature in S3 is 120-160°C and the reaction time is 2-24h.

7. The method according to claim 1, characterized in that: The sintering temperature in S3 is 600-900°C and the sintering time is 1-6 hours.

8. The method according to any one of claims 1 to 7, characterized in that: In the magnesium-doped alumina catalyst carrier, the magnesium content, calculated as MgO, accounts for 0.5-5.0wt% of the total mass of the catalyst carrier.

9. The magnesium-doped alumina catalyst carrier obtained by the method according to any one of claims 1 to 8, characterized in that: Specific surface area is 80-250m 2 / g, pore size is 8-50nm.

10. Use of the magnesium-doped alumina catalyst carrier according to claim 9 in anthraquinone hydrogenation reaction.

Citation Information

Patent Citations

  • Method for preparing superfine mesoporous magnesium aluminate spinel

    CN101565194A

  • Preparation method of isobutyl ketone synthesis catalyst

    CN102416325A

  • Preparation method of alumina carrier

    CN103787388A

  • Template method for preparing catalyst for anthraquinone hydrogenation for producing hydrogen peroxide

    CN107185529A

  • Preparation method of anthraquinone hydrogenation catalyst

    CN109894112A